The Emerging Role of Bone-Derived Hormones in Diabetes Mellitus and Diabetic Kidney Disease - Li, Yixuan; Gu, Zuhua; Wang, Jun; Wang, Yangang; Chen, Xian; Dong, Bingzi (Frontiers in Endocrinology, 2022)
Diabetic kidney disease (DKD) causes the greatest proportion of end-stage renal disease (ESRD)-related mortality and has become a high concern in diabetes mellitus (DM) patients. Recently, bone is concerned as an endocrine organ, playing an emerging role in regulating glucose and energy metabolism. Accumulating research has certificated that bone-derived hormones are involved in glucose metabolism and the pathogenesis of DM complications, especially DKD. Furthermore, these hormones are considered the promising predictor and prospective treatment targets for DM and DKD. In this review, we focused on the bone-derived hormones, including fibroblast growth factor 23 (FGF23), osteocalcin (OCN), sclerostin, and lipocalin 2, and summarized their role in regulating glucose metabolism and DKD.